PENCEGAHAN STUNTING SEJAK DINI MELALUI PEMENUHAN GIZI DAN PERAN KELUARGA DI DESA PULO PANJANG, KABUPATEN SERANG - Desma Yuliadi Saputra; Yania Febsi; Umalihayati Umalihayati; Rina Andriani; Novita Sari; Nurhasan Nugroho (Gapenas Publisher, 2023)
This research describes the relationship between malnutrition issues and stunting in children, with a focus on significant impacts on physical and mental development. Children experiencing stunting have lower average Intelligence Quotient (IQ) scores, affecting productivity and increasing the risk of degenerative diseases in the future. Data from the Ministry of Health indicates a concerning prevalence of stunting in Indonesia, exceeding the tolerance limits set by the World Health Organization. The province of Banten, in particular, shows significant stunting rates. Therefore, this research focuses on stunting prevention efforts through health promotion and community empowerment. Community engagement activities were conducted in Pulo Panjang Village, Serang Regency, involving observation, discussions, and the implementation of educational activities. Research findings indicate that community knowledge about stunting prevention is lacking, primarily due to insufficient support from village officials and limited access to healthcare professionals. During educational activities, leaflets were distributed, and materials were presented using infocus media to enhance community knowledge. Evaluation was performed through Q&A sessions to assess the extent of community understanding. Results from community engagement activities show that the community gained additional knowledge about stunting prevention, particularly through leaflets and educational materials. Awareness of the importance of handwashing with soap as a simple step in stunting prevention was also reinforced. Therefore, these activities are expected to increase community knowledge and awareness of stunting prevention, help reduce stunting rates in the region, and promote positive behavioral changes related to the nutrition and health of children